A COMPILATION OF MOORED CURRENT METER OBSERVATIONS, VOLUME III. - Webster,Ferris; Fofonoff,Nick P. (1967)
Summaries of current measurements made with Richardson current meters in two regions of the Western North Atlantic are presented. Averaged quantities are presented in the form of computer-plotted curves. (Author) See also Volume 2, AD-651 112.